Main framework for developing Sharia economic Fiqh: A contemporary Islamic law reform perspective - Mudawam, Syafaul (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to provide an in-depth analysis of the practical application of Islamic Fiqh principles, particularly in contemporary legal contexts. It focuses on how these principles are implemented in modern legal rulings, ensuring the relevance of classical Islamic Fiqh within the Sharia system upheld by society and the state. The research does not trace the historical evolution of authentication practices, nor does it assess the validity of rulings or the chronological development of Islamic Fiqh. The study employs an analytical approach to examine the extent to which methodological principles of Islamic Fiqh are applied in contemporary legal cases. It does not delve into historical authentication practices or the chronological evolution of Islamic Fiqh but instead focuses on the practical implementation of these principles in resolving modern legal issues. The findings highlight the crucial role of Islamic Fiqh principles as a framework for developing modern legal methodologies. The study demonstrates how these principles continue to guide contemporary legal rulings and ensure the applicability of classical Islamic jurisprudence in the current Sharia-based legal system.